Stress Analysis of the Circular Arc Flexure Hinge - Duan Yanlu; Ou Kailiang; Sun Yinsheng; Tian Ye (Jixie chuandong)
For the application of the flexible hinge in the wind tunnel strain balance calibration system,the circular arc flexure hinges are used as the research object to calculate the maximum stress. The stress of a typical hinge is analyzed and the method which the circular arc flexure hinge is equal to straight round flexure hinge is presented. Based on the stress concentration theory,the stress concentration coefficient formulas of hinge are fitted when the hinge is applied axial force and bending moment respectively. The three dimensional models of different parameters are established,and the finite element simulation analysis is carried out by using ANSYS Wrokbench. The simulation data and theoretical calculation data are compared to verify the feasibility of the equivalent method and the fitting formulas.